INTEGRATION OF CROP-LIVESTOCK-BIOGAS AND THE EFFECT OF DRIED SLUDGE MANURE ON THE GROWTH AND YIELD OF MAIZE ON ULTISOL SOIL - Soelaeman, Yoyo; Maswar, Maswar (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
The study was conducted in 2012 and 2013 in Tamanbogo Experimental Farm consists of 3 activities, namely 1). To evaluate the kind and amount of feed consumed by 20 heads of cattle and the amount of manure produced, 2). To evaluate the amount of biogas, sludge and slurry produced by digester, and 3). To study the application of manure, dried sludge manure, and NPK fertilization on the growth and yield of hybrid maize of Pioneer 27 (P27). The research results showed that the total weight of feed consumed in the rainy season and in the dry season has already achieved to the recommendation of 10% of the body weight of cattle. The average production of manure and urine were 11.25 kg head-1 day-1 with the biogas production of 3 m3 day-1 was sufficient for cooking and lighting for 5 members of family daily. The by-product of biogas production was 8 kg day-1 of sludge and 127 L day-1 of slurry. The grain yield of P27 with application of dried sludge accompanied with 50 % of NPK fertilizer recommendation dose gave the highest yield of P27 (4.45 t ha-1) with a profit Rp. 3,466,000 ha-1 and B/C of 1.5